Health economics from theory to practice : optimally informing joint decisions of research, reimbursement and regulation with health system budget constraints and community objectives /: optimally informing joint decisions of research, reimbursement and regulation with health system budget constraints and community objectives. ([2017]) - Eckermann, Simon
No abstract available